ATORVASTATIN LOADING DOSE BEFORE INTRACORONARY INTERVENTION PROVIDES PROTECTIVE EFFECT IN PATIENTS WITH CHRONIC ATHEROSCLEROTIC TOTAL OCCLUSION OF CORONARY ARTERIES - A. S. Ragozina; I. V. Petrenko; I. A. Urvantseva; S. I. Pavlov; K. Yu. Nikolaev (Атеросклероз, 2018)
Objective. To analyze the protective effect of atorvastatin loading dose on the reduction of myocardial injury associated with percutaneous coronary intervention, left ventricular systolic functionand exercise tolerancein patients with endovascular recanalization of chronic atherosclerotic total occlusions. Methods. 82 patients underwent recanalization. The patients in the main group ( n = 38) received a loading dose of atorvastatin 80 mg before surgery. Patients in control group ( n = 44) received 20 mg of atorvastatin. In both groups Troponin I, CF fraction of creatine phosphokinaseweremeasured, echocardiographyand veloergometer test were performed prior to surgery, 24 hours, 1 month, 1 year after the surgery. Results. There was no difference in Troponin I and CF fraction of creatine phosphokinase initial levels. In 24 hours in the main group in 3 patients (7,9 %) there was discovered moderate troponin I rising. In the control group there were 11 (25 %) patients with increasing in troponin I level in 5 and more times. CF fraction of creatine phosphokinase in control group was increased in 3 (7,9 %) patients, in the control group this parameter was increased in 16 (36,4 %) patients. In 1 month and 1 year Troponin Iand CF fraction of creatine phosphokinaselevel was normal in the both groups.There were no statistically significant changes in echocardiography parametersor exercise tolerance during the all follow-up period. Conclusion. Atorvastatin loading dose has a protective effect and prevents periprocedural myocardial injury. At the same time it doesn’t influence on central hemodynamics parameters measured by echocardiography.